Reconstructing Boulder Deposition Histories: Extreme Wave Signatures on a Complex Rocky Shoreline of Malta - Derek. N. Mottershead; Philip J. Soar; Malcolm J. Bray; Linley J. Hastewell (Geosciences, 2020)
The Żonqor coastline, southeast Malta, displays an exceptional range of geomorphic signatures of extreme coastal events. This paper brings together evidence acquired from a field survey, analysis of time-sequential imagery, and hydrodynamic modelling to investigate the histories of boulder groups identified by their intrinsic and contextual characteristics. Clear differences are revealed between the distribution of boulders recently moved and those of considerable age. Tracking the movement of boulders since 1957 confirms that storms of surprisingly frequent interval are capable of complex boulder movements, including lifting of megaclasts. Scrutiny of the ancient boulders, including weathering features and fascinating landward-facing (reverse) imbrication, cautiously suggests tsunami as the agent for their emplacement. A novel method is developed for depicting the velocity decay profiles of hypothetical waves, which overcomes some of the limitations of the Nott approach. Applied here, the wave run-up context further sets the ancient movers apart from their recent mover companions. The combined evidence implies a palimpsestic landscape where storm waves are regular geomorphic agents that add to and rework the distribution of boulders close to the shoreline, but over long time periods the landscape becomes reset by tsunami—a concept that is of value to agencies in Malta responsible for coastal safety, planning and management.